Unnamed Partners From Syphilis Partner Services Interviews, 7 Jurisdictions. Issue 12 (December 2020) - Cope, Anna Barry; Bernstein, Kyle; Matthias, James; Rahman, Mohammad; Diesel, Jill; Pugsley, River A.; Schillinger, Julia A.; Ng, Rilene A. Chew; Sachdev, Darpun; Shaw, Rebecca; Nguyen, Trang Quyen; Klingler, Ellen J.; et al.
Abstract : Background: Reducing transmission depends on the percentage of infected partners treated; if many are missed, impact on transmission will be low. Traditional partner services metrics evaluate the number of partners found and treated. We estimated the proportion of partners of syphilis patients not locatable for intervention. Methods: We reviewed records of early syphilis cases (primary, secondary, early latent) reported in 2015 to 2017 in 7 jurisdictions (Florida, Louisiana, Michigan, North Carolina, Virginia, New York City, and San Francisco). Among interviewed syphilis patients, we determined the proportion who reported named partners (with locating information), reported unnamed partners (no locating information), and did not report partners. For patients with no reported partners, we estimated their range of unreported partners to be between one and the average number of partners for patients who reported partners. Results: Among 29, 719 syphilis patients, 23, 613 (80%) were interviewed and 18, 581 (63%) reported 84, 224 sex partners (average, 4.5; 20, 853 [25%] named and 63, 371 [75%] unnamed). An estimated 11, 138 to 54, 521 partners were unreported. Thus, 74, 509 to 117, 892 (of 95, 362–138, 745) partners were not reached by partner services (78%–85%). Among interviewed patients, 71% reported ≥1 unnamed partner or reported no partners; this proportion was higher for men who reported sex with men (75%) compared with men who reported sex with women only (65%) and women (44%). Conclusions: Approximately 80% of sex partners were either unnamed or unreported. Partner services may be less successful at interrupting transmission in networks for men who reported sex with men where a higher proportion of partners are unnamed or unreported. Abstract : Among partner services programs in 7 US jurisdictions, most sex partners of early syphilis patients (80%) are unlocatable or unreported, limiting the potential for partners services to intervene on transmission.Supplemental digital content is available in the text.